BCR-ABL fusion genes and laboratory findings in patients with chronic myeloid leukemia in northeast Iran - Hossein Ayatollahi; Mohammadreza Keramati; Abbass Shirdel; Mohammadmehdi Kooshyar; Majid Raeiszadeh; Sepideh Shakeri; Mohammadhadi Sadeghian; Fatemeh Shams (Babol University of Medical Sciences, 2018)
Background: A specific chromosomal abnormality, the Philadelphia chromosome (BCR-ABL fusion), is present in all patients with chronic myeloid leukemia (CML). The b2a2 and b3a2 fusion mRNAs encode p210 fusion protein p210 and e1a2 encode p190. The aim of this study was to evaluate the frequency of BCR-ABL fusion transcript variants in Northeast of Iranian CML patients and to compare the laboratory results of our patients. Methods: This study was conducted in 85 peripheral blood and bone marrow samples of CML patients. Ribonucleic acid (RNA) was extracted by a commercial kit, RT- PCR for identifying BCR-ABL fusions was carried out by using designed primers and the PCR products were electrophoresed in agarose gels. Finally, statistical analysis was performed for variant frequency identification and their comparison was performed. Results: All patients examined were positive for BCR/ABL rearrangement. Fusion of b3a2 was detected in 53 (62.35%) patients, b2a2 in 25 (29.41), e1a2 in 1 (1.17%) and coexpression of b3a2 and e1a2 in 6 (7.05%) patients. There were significant differences between the mean age in patients with b3a2 positive ( 44.07 years) and in b3a2 negative group (50.35 years) however, no significant differences were seen between sex and b2a2 (P=0.61), b3a2 (P=0.79) and e1a2 (P=0.20). Conclusions: This study showed higher frequency b3a2 than b2a2 and e1a2 transcripts in CML patients in Northeast Iran and there was no association between e1a2 transcripts frequencies and monocytosis in peripheral blood